Μελέτη του μηχανισμού αστοχίας των υλικών με χρήση του συστήματος Vic-2d σε πειράματα τύπου βραζιλιανής δοκιμής - Κωστέλλος, Ηλίας (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών. Τομέας Έργων Υποδομής και Αγροτικής Ανάπτυξης, 2018)
Objective of this work is the intrerpretation of the fail mechanism of the materials through the study of the crushing their samples in the laboratory. The section of Technical Engineering that will help us is Crashing Engineering and via its methods can interpret the fail mechanism of materials like concrete and mortars which present discontinuity in their structure. For this reason a series of Brazilian Type experiments have been occurred in the laboratory, using a variety of materials like gypsum , mortar which is reinforced with fiberglass. For the simulation of the crushing procedure and the results, a new method uses digital image correlation via the Vic-2d system and through this method, numerically results for the displacements extracted.